OP0071 The prevalence of pain flares: impact of definition. (12th June 2018) - Beukenhorst, A.L.; McBeth, J.; Sergeant, J.C.; Schultz, D.M.; Dixon, W.G.
Abstract : Background: Rapid acute pain exacerbations, colloquially called pain flares, affect quality of life and are a key driver for patients to seek healthcare. There is no standardised definition of pain flare. 1 Daily collection of patient-reported symptoms with mobile technology enables monitoring pain flares in real-time. The choice of definition may identify different people and patterns of pain severity. If remote monitoring of flares is to inform clinical practice and research, it is important to understand the implications of these choices. Objectives: Investigate the frequency of pain flares from daily pain symptoms under various definitions in a population with chronic pain. Methods: Participants with chronic (≥3 months) musculoskeletal pain in the smartphone study Cloudy with a Chance of Pain 2 reported daily pain severity and impact of pain on a 5-point scale. Pain flares were defined in five ways: 1. Worse than average: pain severity higher than personal median 2. Above threshold: pain value 4 or 5 3. Move to above threshold: pain value 1 or 2 or 3 yesterday to 4 or 5 today 4. Absolute change: 2-point increase in pain since yesterday 5. Composite: 2-point increase in pain severity since yesterday and impact 4 or 5 Daily pain-flare rate was calculated by dividing the number of pain flares by the number of days a pain flare would have been possible, hereafter called at-risk days (def. 1+2: total days of symptom entry; def 3 to 5: days of data entry for which participant also entered data on preceding day). Monthly pain-flare rates per person were calculated by multiplying the rate by 30. Results: The study smartphone app was downloaded by 13 256 people. After excluding people that never reported pain severity (n=2020), did not complete the baseline questionnaire (n=947), stayed in the study for less than 7 days (n=3418), and reported non-musculoskeletal chronic pain (n=728), 6143 were eligible for analysis. Table 1 shows that the portion of eligible people with at least one pain flare varies by definition, with 42% reporting at least one pain flare according to the most restrictive classification criterion. Depending on the criterion used, the monthly pain-flare rate per ranges from 0.9 to 8.7. Under the 'worse than average' and 'above threshold' definition, most participants have more than 10 pain flares per month (figure 1). Under the two most stringent definitions, most participants have between 0 and 3 pain flares per month. Conclusions: The five plausible definitions for a pain flare are demonstrated to generate quite different flare rates through time. Pain flares in people with chronic musculoskeletal pain, however, remain common even as classification criteria become increasingly strict. As daily data collection of patient-generated data becomes possible, careful thought must be given to flares should best be defined for clinical practice and research. References: [1] Gossec L, et al. doi:10.1136/annrheumdis-2015-208593 [2] Druce KL, et al. doi:10.2196/mhealth.8162 Disclosure of Interest: None declared